GREEN MUSSEL (Perna viridis) AND SILKWORM (Tubifex sp.) FEEDING TRIAL AS AN ALTERNATIVE FEED FOR CRAYFISH SEEDS (Cherax quadricarinatus) - Fajar Kusuma, Andrean; Farikhah, Farikhah; Aminin, Aminin (Kontribusia : Research Dissemination for Community Development, 2021)
The high cost of shrimp or lobster feed is also a problem in the sustainability of aquaculture, even though freshwater crayfish, including eaters, require proper and relatively cheap feed selection. One source of feed that can be used as an alternative is green clams and silk worms. This study aims to determine which feed is better and more affordable for freshwater lobster seeds, so that the sustainability of cultivation can be well maintained in terms of economy, quality and quantity. The method used was descriptive comparing between the two feeds given a dose of each treatment, namely 10% of the lobster seed biomass, then analyzed using a 95% confidence level t-test. The results showed a significant effect (P <0.05), on the absolute length growth and absolute weight of freshwater lobster seeds. The absolute length of the seeds given green shellfish feed is 0.94 ± 0.38 cm and silkworm feed is 0.66 ± 0.27 cm, for the absolute weight of green shellfish feed is 5.11 ± 0.38 gr and silk worm feed 2.68 ± 0.18 gr. The best results from the two feeding treatments for freshwater lobster seeds were using green shellfish feed with an absolute weight value of 5.11 ± 0.38 gr and the absolute length is 0.94 ± 0.38 cm. So that green shellfish feed can be used as a better alternative feed for the cultivation of freshwater lobster seed enlargement.